Singapore : Detailed Assessment of Compliance on the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report, 2013)
This paper discusses key findings of the Detailed Assessment of Compliance on the Basel Core Principles for Effective Banking Supervision on Singapore. The assessment of the Monetary Authority of Singapore (MAS) represents a very high level of compliance with the Basel Core Principles for Effective Banking Supervision and demonstrates a strong commitment by MAS to their implementation. MAS is well aware of the risks posed by a financial system that is significantly larger than the economy of Singapore. MAS has also set a high standard for approving foreign entrants, applying the same prudential framework to foreign branches as to its own locally incorporated banks.